ANALISIS FAKTOR-FAKTOR PERILAKU DOSEN DALAM MENGAJAR MENURUT PERSEPSI MAHASISWA JURUSAN ADMINISTRASI NIAGA - Esya Alhadi; Rini Rini; Elisa Elisa (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
The purpose of this research is to know the perception of student Business Administration of State Polytechnic of Sriwijaya towards lecturer behavior in teaching. The data were collected by using a questionnaire, and analyzed with cartisius diagram. The results showed that the expection value is grater then the value of the fact, that implied 3,57 and 2,93. This shows that satisfaction or fact regarding behavior in the teaching according to the perceptions of students still below the standard expected. Some of the lecturers teaching behaviors that should be preserved is the matery of materials, the ability to communicate in the classroom, time to discuss, don’t smoke while teaching, always dress modestly at time when teaching, polite attitude at a time when teaching, interspersed with moments of humor, friendly teaching attitude towards students, and questions to be tested in accordance with study materials. While the factors that need to be repaired from the lecturer behavior in the teaching is less able to manage interaction among students in teaching and learning processes, student do not have time to ask to the lecturer in learning procceses, less honest in assessing students’ behavior and discriminate between students, lecturers are not transparent in marking, lecturer are not timely in accomplishing all the material given in a semester.